REALISTIC MATHEMATICS EDUCATION (RME) BERBASIS BLANDED LEARNING DALAM PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA - Ira Vahlia; Uminarsih _ (Jurnal Karya Pendidikan Matematika, 2019)
The research objective is to improve student mathematics learning outcomes by applying the Realistic Mathematic Education (RME) approach. This type of research method is Classroom Action Research (CAR) which is carried out in 2 cycles with stages of each cycle namely planning, implementing, observing, and reflecting. Data collection techniques in the form of non-test techniques and test techniques. Data collection tool uses observation sheets and formative tests. Data analysis techniques using qualitative analysis techniques and quantitative analysis. Increasing the percentage of students' KKM completeness learning outcomes from pre-action activities and each cycle. The average increase in student learning outcomes from pre-action was 51.07, whereas in the first cycle the average learning outcomes were 78.85 and the second cycle was an average learning outcomes of 83.55. The results showed that the application of the RME approach could improve mathematics learning outcomes of students of class XI of SMA N 3 Metro.